The Strength of Islamic Values in Mentoring Entrepreneurs among Lecturers: A Qualitative Study - Hashim, Noraini; Ab Wahid, Hariyaty (EDUCATUM Journal of Social Sciences, 2024)
This article is about the study of Islamic values in mentoring start-up entrepreneurs by lecturers. This study was conducted to explore how attachment to Islamic values can be a strength for mentors in the mentoring process. The research method used was qualitative, using an in-depth, semi-structured interview protocol validated by four inter-raters, and Cohen’s Kappa rating was 1.00. The empirical finding in this study is that Islamic values greatly help lecturers become good mentors in guiding and supporting the development of entrepreneurs at the IPT. The main message is that, by adhering to Islamic values, it improves the mentoring process of entrepreneurs among lecturers. The new discovery in this study is that it focuses on the values of mentors and not entrepreneurs. The implications of this research are that it can help universities and organisations develop mentoring programmes that incorporate Islamic values to improve entrepreneurial mentoring processes. Keywords: entrepreneurship, mentorship, mentor’s competencies, lecturers, Islamic value